The divergent roles of autophagy in ischemia and preconditioning - SHENG Rui; QIN Zheng-hong (Acta Pharmacologica Sinica, 2017)
Autophagy is an evolutionarily conserved and lysosome-dependent process for degrading and recycling cellular constituents. Autophagy is activated following an ischemic insult or preconditioning, but it may exert dual roles in cell death or survival during these two processes. Preconditioning or lethal ischemia may trigger autophagy via multiple signaling pathways involving endoplasmic reticulum (ER) stress, AMPK/TSC/mTOR, Beclin 1/BNIP3/SPK2, and FoxO/NF-κB transcription factors, etc. Autophagy then interacts with apoptotic and necrotic signaling pathways to regulate cell death. Autophagy may also maintain cell function by removing protein aggregates or damaged mitochondria. To date, the dual roles of autophagy in ischemia and preconditioning have not been fully clarified. The purpose of the present review is to summarize the recent progress in the mechanisms underlying autophagy activation during ischemia and preconditioning. A better understanding of the dual effects of autophagy in ischemia and preconditioning could help to develop new strategies for the preventive treatment of ischemia.